2020
DOI: 10.1002/ejoc.201901576
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on Concentrated Lithium Salt/Nitroalkane Electrolyte Based on Analogy with Fluorinated Alcohols

Abstract: Fluorinated alcohols such as 1,1,1,3,3,3-hexafluoro2propanol (HFIP) and 2,2,2-trifluoroethanol (TFE) have emerged as powerful solvents in oxidation chemistry including hole catalysis. In this paper, we describe the similarity of lithium salt/ nitroalkane electrolytes with fluorinated alcohols in electrosynthesis. Based on the results from electrosynthesis, Raman and nuclear magnetic resonance spectroscopy and cyclic voltammetry (CV), we have demonstrated that the combination of lithiumRecently, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Previously, we revealed that HFIP could trap anionic species via its hydrogen bond acceptor property, generating reactive “intact” radical cations under electrochemical conditions [4b] . Furthermore, we recently reported that the concentrated MeNO 2 –LiClO 4 system exhibits the identical acceleration effect via its unique solvent clustering, which was detected using Raman spectroscopy [7e] . Therefore, the MeNO 2 ‐HFIP mixed solvent system is a suitable medium for the intramolecular cross‐coupling reactions of N ‐benzoyl indolines, as demonstrated by the successful total syntheses of pyrrolophenanthridone alkaloids [10] .…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we revealed that HFIP could trap anionic species via its hydrogen bond acceptor property, generating reactive “intact” radical cations under electrochemical conditions [4b] . Furthermore, we recently reported that the concentrated MeNO 2 –LiClO 4 system exhibits the identical acceleration effect via its unique solvent clustering, which was detected using Raman spectroscopy [7e] . Therefore, the MeNO 2 ‐HFIP mixed solvent system is a suitable medium for the intramolecular cross‐coupling reactions of N ‐benzoyl indolines, as demonstrated by the successful total syntheses of pyrrolophenanthridone alkaloids [10] .…”
Section: Resultsmentioning
confidence: 98%
“…We analyzed the LiX/nitroalkane electrolyte using Raman spectroscopy. 22 Fig. 5b shows representative data for LiClO 4 /CH 3 NO 2 electrolyte in the concentration range of 0.1 ~ 2.0 M. A broad absorption band at 942 cm -1 appeared with increasing concentration of LiClO 4 (Fig.…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…4). 22 To highlight the difference in efficiency of hole catalysis depending on the concentration of Li salts in the electrolytes, the electrolysis was intentionally stopped after the passage of 0.03 F/mol of charge (equals to 0.03 electron oxidation per trans-anethole). In other words, the reaction was quenched before the complete consumption of the starting materials.…”
Section: Electrolyte Design Based On a Concentrated Lix/nitroalkanementioning
confidence: 99%
“…We have developed radical cation cycloadditions using (photo)electrochemical single-electron transfer in lithium per- chlorate (LiClO 4 )/nitromethane (CH 3 NO 2 ) solution [36][37][38][39][40][41][42][43][44]. During the course of our studies, we found that the TiO 2 photoelectrochemical approach was more beneficial than simple electrochemistry in most cases, probably because both single-electron oxidation and reduction are made possible at the same surface [45].…”
Section: Introductionmentioning
confidence: 99%